In Situ Activation/Dedoping‐Induced Defective Carbon Sponge for Enhanced Oxygen Reduction Electrocatalysis. Issue 24 (16th December 2021) - Wei, Keyan; Zheng, Hongmei; Hou, Jingting; Tang, Zeming; Zheng, Jing; Lai, Qingxue; Liang, Yanyu
Abstract: The N‐dedoping‐based defect engineering strategy has been designed as an efficient method to develop advanced defective carbon electrocatalysts for the oxygen reduction reaction (ORR). However, the defective structures, especially the defect density of carbon materials fabricated by this method, were significantly suppressed by the limited N doping level. Herein, an in situ activation/N‐dedoping strategy was proposed to fabricate a controllable defective carbon sponge (DCS) for ORR electrocatalysts, during which a Schiff‐base polymer with a high N content was employed as the carbon precursor and N source while zinc oxide (ZnO) nanoparticles were the thermally removable structure template and activator. As a result, the optimized DCS1100 with a high specific surface area of 1198 m 2 /g and a low nitrogen content of 2.81 at.% delivered a comparable activity and four‐electron selectivity but superior stability to commercial 30 % Pt/C in 0.1 M KOH electrolyte. Abstract : Soak it up : In situ activation/dedoping induces conversion to produce high‐activity and high‐density defective carbon materials, which are used to enhance oxygen reduction performance.